2002
DOI: 10.1152/ajpgi.00365.2001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between esophageal muscle thickness and intraluminal pressure in patients with esophageal spasm

Abstract: . Relationship between esophageal muscle thickness and intraluminal pressure in patients with esophageal spasm. Am J Physiol Gastrointest Liver Physiol 282: G1016-G1023, 2002 10.1152/ ajpgi.00365.2001.-We previously showed, in normal subjects, a positive correlation between the esophageal contraction amplitude and peak muscle thickness. The goal of this study was to determine the relationship between esophageal muscle thickness and contraction amplitude in patients with highamplitude peristaltic and simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 22 publications
(19 reference statements)
2
37
0
Order By: Relevance
“…These results support the physiological explanation of longitudinal muscle function discussed above, since a higher degree of LLS would imply a higher concentration of circular muscle fibers and, potentially, a higher closure pressure (equation 1, Figure 4). Pehlivanov et al [23] went on to show that this correlation weakens in patients with nutcracker esophagus and diffuse esophageal spasm, suggesting that pathology of circular and longitudinal muscle during bolus transport may be intertwined. Interestingly, Balaban et al [24] demonstrated a correlation in thickening of the esophageal muscularis propria sustained for a minute and chest pain, in the absence of peristalsis and circular muscle contraction.…”
Section: Related Observationsmentioning
confidence: 99%
“…These results support the physiological explanation of longitudinal muscle function discussed above, since a higher degree of LLS would imply a higher concentration of circular muscle fibers and, potentially, a higher closure pressure (equation 1, Figure 4). Pehlivanov et al [23] went on to show that this correlation weakens in patients with nutcracker esophagus and diffuse esophageal spasm, suggesting that pathology of circular and longitudinal muscle during bolus transport may be intertwined. Interestingly, Balaban et al [24] demonstrated a correlation in thickening of the esophageal muscularis propria sustained for a minute and chest pain, in the absence of peristalsis and circular muscle contraction.…”
Section: Related Observationsmentioning
confidence: 99%
“…Recent observations by Pehlivanov et al [7] using high-frequency intraluminal ultrasound suggest that there is increased esophageal smooth muscle thickness in DES patients. Even in the absence of esophageal contractions, the muscularis propria was thicker in DES patients than in controls and patients with nonspecific motor disorders.…”
Section: Esophageal Muscle Thicknessmentioning
confidence: 99%
“…Studies combining esophageal manometry and high-frequency ultrasound have shown the presence of hypertrophy of the muscularis propria in patients with hypertensive contractions [15,25]. Asynchrony between the circular and longitudinal esophageal muscle contractions has also been demonstrated in patients with NE [25,26].…”
Section: Diagnosismentioning
confidence: 99%
“…Unfortunately, there are scarce histopathologic studies from patients with DES, and the findings are nonspecific [13,14]. Studies with endoscopic ultrasound have shown that patients with DES have a thicker muscularis propria layer than controls [14,15]. Also, 31-33 % of cases with DES demonstrate GERD [4•,16].…”
Section: Distal Esophageal Spasmmentioning
confidence: 99%